P03.23 Evolution of the immune landscape within partially controlled murine melanoma. (1st October 2020) - Qing, C; Ghorani, E; Solomon, I; Gálvez-Cancino, F; Vargas, F; Peggs, K; Quezada, S
Abstract : Background: Regulatory T cell (Treg) depletion with antibodies against CD25 is effective in tumor models but response rates are low in poorly infiltrated B16 melanomas. Combination with a tumor vaccine enhances efficacy, but relapse usually occurs following partial control, similar to what is seen clinically. How resistance develops is unknown. Materials and Methods: C57BL/6 mice were injected subcutaneously with B16 cells. Treatments included a depleting mouse IgG2a αCD25 antibody and/or a genetically modified, granulocyte-macrophage colony-stimulating factor (GM-CSF) secreting whole B16 tumor vaccine (Gvax). Changes in the immune landscape were assessed with high dimensional flow cytometry. Results: Compared to monotherapies, combined Gvax/αCD25 significantly delayed tumour growth and prolonged survival, in association with enhanced infiltration of T cells with an activated phenotype. Approximately 50% of mice achieved partial response with relapse at day 35–45 post tumor injection. To characterize immune evolution prior to relapse, we analysed stable, partially responding tumors and paired draining lymph nodes (DLNs). Over time, activated PD-1+ICOS+TCF7- T cells with an effector memory (CD44+CD62L-) phenotype fell from 30% to 10% whilst resting, TCF7+ early differentiated cells rose in abundance towards levels seen in untreated tumors. Abundance of Ki67-, resting Tregs also recovered. Similar results were obtained in analysis of DLNs. Conclusions: Combined Treg depletion/whole tumor vaccination therapy is effective in a poorly infiltrated B16 melanoma model. Combined treatment promotes T cell infiltration and activation. In mice achieving a partial response, treatment effects on the immune landscape were observed to decay over time suggesting a return to immune equilibrium. Further studies to explore the mechanistic basis of this observation are underway. Disclosure Information: C. Qing: None. E. Ghorani: None. I. Solomon: None. F. Gálvez-Cancino: None. F. Vargas: None. K. Peggs: None. S. Quezada: B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Significant; F. HOFFMANN-LA ROCHE LTD.